A Rice Brassinosteroid-Deficient Mutant, ebisu dwarf (d2), Is Caused by a Loss of Function of a New Member of Cytochrome P450 - Hong, Zhi (American Society of Plant Biologists, 2003)
We characterized a rice dwarf mutant, ebisu dwarf (d2). It showed the pleiotropic abnormal phenotype similar to that of the rice brassinosteroid (BR)-insensitive mutant, d61. The dwarf phenotype of d2 was rescued by exogenous brassinolide treatment. The accumulation profile of BR intermediates in the d2 mutants confirmed that these plants are deficient in late BR biosynthesis. We cloned the D2 gene by map-based cloning. The D2 gene encoded a novel cytochrome P450 classified in CYP90D that is highly similar to the reported BR synthesis enzymes. Introduction of the wild D2 gene into d2-1 rescued the abnormal phenotype of the mutants. In feeding experiments, 3-dehydro-6-deoxoteasterone, 3-dehydroteasterone, and brassinolide effectively caused the lamina joints of the d2 plants to bend, whereas more upstream compounds did not cause bending. Based on these results, we conclude that D2/CYP90D2 catalyzes the steps from 6-deoxoteasterone to 3-dehydro-6-deoxoteasterone and from teasterone to 3-dehydroteasterone in the late BR biosynthesis pathway.